Ophichthus chilkensis Chaudhuri, 1916 (Anguilliformes: Ophichthidae)—resurrection as a valid species from India, with re-description - Mishra, Subhrendu Sekhar; Mohapatra, Anil; Ray, Dipanjan; Mohanty, Swarup Ranjan; Tudu, Prasad C. (Zootaxa, 2019)
Ophichthus chilkensis Chaudhuri, 1916 has long been treated as a synonym of Pisodonophis cancrivorus (Richardson, 1848). O. chilkensis is hereby re-described on the basis of holotype from Chilika Lake, Odisha as well as ten fresh specimens from Talsari, Balasore district, Odisha and Digha, West Bengal. The present study confirms it belonging to the genus Ophichthus and resurrected as a valid species from the east coast of India. It is compared with its closest congener species, particularly with Ophichthus microcephalus Day, 1878, known from India.